Coordinated Development of Regional Complex System: A Niche-Based Study - Jianling Li; Xiang Fan; Yufei Bai; Jingjing Zhang (Discrete Dynamics in Nature and Society)
Taking Beijing-Tianjin-Hebei as an example, it analyzes the comprehensive competitiveness of Beijing, Tianjin, and Hebei. It selects four dimensions: economic dimension, social dimension, environmental dimension, and technological dimension. From a new perspective, it explores the application of niche theory in regional synergy. Based on the analysis of the ecological niche, the coordination degree model of the composite system is further used to calculate the status quo of the coordinated development of the Beijing-Tianjin-Hebei region from 2013 to 2019. The results show that Beijing has the highest ecological niche, followed by Tianjin, and Hebei is the weakest. In 2019, the Beijing-Tianjin-Hebei region is at a good level of coordination, with the social subsystem having the highest order and the technological subsystem having the lowest order. Based on this, it is proposed that the Beijing-Tianjin-Hebei regions should be scientifically positioned, the overall need to be aligned with international trends, and the internal planning should be integrated to further enhance the level of cooperation in the Beijing-Tianjin-Hebei region.